Optimization of transpeptidation reaction of the insulin precursor for efficient yield recovery during downstream processing - Ali, Syed Morsalin (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of M.Sc in Biotechnology, 2017.